Evolutionary game study on multi-agent collaboration of digital transformation in service-oriented manufacturing value chain - Gao, Jing; Zhang, Wanfei; Guan, Tao; Feng, Qiuhong (Electronic commerce research, 2023)
As a development trend of cross-border integration of industries in the digital economy, service-oriented manufacturing has achieved certain research results in the construction of wide value chain. However, in the transition development stage, the collaborative efficiency problem of service-oriented manufacturing value co-creation is increasingly prominent due to the unbalanced development of digitalization level of heterogeneous subjects. Therefore, based on the perspective of various subjects in the value chain of service-oriented manufacturing, this paper analyzes the synergistic mechanism of value co-creation of core manufacturing, service enterprises and customers under the influence of digitalization level difference. Then the paper constructs a three-party digital cooperative evolution game model and uses Netlogo software to simulation analyse. The results reveal the collaborative path of service-oriented manufacturing digital transformation. According to the comparison of the paths of actual enterprises, it is found that the paths has universality, which provide strategic reference for service-oriented manufacturing digital transformation.